Contemporary Problems in Mathematical Physics 2004
DOI: 10.1142/9789812702487_0011
|View full text |Cite
|
Sign up to set email alerts
|

The Cosmological Constant of One-Dimensional Matter Coupled Quantum Gravity Is Quantised

Abstract: Coupling any interacting quantum mechanical system to gravity in one (time) dimension requires the cosmological constant to belong to the matter energy spectrum and thus to be quantised, even though the gravity sector is free of any quantum dynamics. Furthermore, physical states are also confined to the subspace of the matter quantum states for which the energy coincides with the value of the cosmological constant. These general facts are illustrated through some simple examples. The physical projector quantis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…To this purpose let us recall that it is natural for physical gauge invariant states to carry a dependence on the values of the free parameters. This can be seen in two simple examples discussed in detail in [8]. If we consider the case of 0+1 gravity with a cosmological constant coupled with a generic matter sector it can be easily shown that the cosmological constant value must coincide with the energy of the solution at the classical level.…”
Section: The Cosmological Constant In a Quantum Theory Of Gravitymentioning
confidence: 89%
See 1 more Smart Citation
“…To this purpose let us recall that it is natural for physical gauge invariant states to carry a dependence on the values of the free parameters. This can be seen in two simple examples discussed in detail in [8]. If we consider the case of 0+1 gravity with a cosmological constant coupled with a generic matter sector it can be easily shown that the cosmological constant value must coincide with the energy of the solution at the classical level.…”
Section: The Cosmological Constant In a Quantum Theory Of Gravitymentioning
confidence: 89%
“…In a generalization of the one-dimensional and the two-dimensional Liouville gravity cases [5,8] it is interesting to look at the case of two-dimensional dilaton gravity. Two-dimensional generalized dilaton theories provide a very interesting class of models, widely studied in the last two decades.…”
Section: D Dilaton Maxwell Gravity Coupled With Scalar Mattermentioning
confidence: 99%
“…Here, is a real constant of the same physical dimension as L (and H), playing the rôle of a cosmological constant on the world-line [16].…”
Section: World-line Quantization and Physical Statesmentioning
confidence: 99%
“…The associated Noether symmetry, the generator of local world-line gauge transformations, is the extended Hamiltonian and becomes a first class constraint. Following the Dirac quantisation procedure, imposition of the first class constraint on physical states enforces the condition that the cosmological constant term, allowed by the reparametrisation invariant coupling of the system to the world-line metric, must be identified with a discrete fixed eigenvalue of the quadratic Casimir invariant of the quaplectic algebra, in line with well understood features of Hamiltonian quantisation [14]. The decomposition of such irreducible representations of the full quaplectic group with respect to the physical Poincaré group IO(D−1, 1) ∼ = O(D−1, 1)⋉T (D) is discussed, where the generators P µ are identified with the standard energy-momentum operators, the generators of spacetime translations.…”
Section: Introductionmentioning
confidence: 99%
“…The state space of the system (before imposition of the constraint) corresponds to the direct product of two independent D-dimensional Heisenberg algebras -one generated by the conserved generators X µ , P ν of translations in the original 'position' and 'momentum' worldline coordinates, and a second auxiliary, non-conserved set X µ , P ν (both sets have the same central extension, the conserved θ-momentum, Π θ ). Imposition of the first class constraint, the generator of local time reparametrisations, on physical state space enforces identification [10] of the world-line cosmological constant Λ in the model, with a fixed value of the quadratic Casimir of the quaplectic symmetry group. However, both sets of Heisenberg generators provide the material for the construction of the (conserved) generators of the homogeneous U (D−1, 1) component of the quaplectic algebra,…”
Section: Introductionmentioning
confidence: 99%